The dynamics of Wnt-5a and Shh expression in tissue regeneration process of mice (Mus musculus) digit tip - Titta Novianti; Febriana Dwi Wahyuni; Syafruddin Ilyas (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.